Google Books as Infrastructure of In/Justice - Hoffmann, Anthony L (AoIR Selected Papers of Internet Research, 2013)
To date, Google Books has scanned and made searchable more than 20 million books from library collections around the world. Proponents of the project tout its potential for promoting social justice and equality through increased information access. Critics, however, have argued that unresolved issues with regard to privacy, copyright, and censorship ultimately subvert the values the project claims to further. These controversies reveal Google Books as a rich example of the complex relations infrastructures establish between technologies, institutions, and individuals. Current debates, however, have concentrated on the interests of the project’s stakeholders, overlooking Google Books as sociotechnical infrastructure—that is, as a set of relations mobilized in practice. Employing the method of “infrastructural inversion” (Bowker, 1994), this paper examines the interdependence between technologies and social practices organized by Google and inquires whether or not the “egalitarianism of information” touted by Google is rendered possible by the sociotechnical relations it mobilizes.